The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/cas.13390
|View full text |Cite
|
Sign up to set email alerts
|

miR‐125b‐1 and miR‐378a are predictive biomarkers for the efficacy of vaccine treatment against colorectal cancer

Abstract: Many clinical trials of peptide vaccines have been conducted. However, these vaccines have provided clinical benefits in only a small fraction of patients. The purpose of the present study was to explore microRNAs (miRNAs) as novel predictive biomarkers for the efficacy of vaccine treatment against colorectal cancer. First, we carried out microarray analysis of pretreatment cancer tissues in a phase I study, in which peptide vaccines alone were given. Candidate miRNAs were selected by comparison of the better … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 55 publications
1
28
0
Order By: Relevance
“…D'Angelo et al reported that high miR-125b expression in tissue and serum was associated with a poor treatment response in locally advanced rectal cancer (30). Interestingly, Tanaka et al identified miR-125b-1 expression in cancer tissues as a predictive biomarker for the efficacy of peptide vaccine treatment against CRC (31). However, our study is the first to demonstrate the potential of plasma ex-miR-125b as a biomarker for the early detection of resistance to mFOLFOX6-based chemotherapy in advanced/recurrent CRC.…”
Section: Discussionmentioning
confidence: 61%
“…D'Angelo et al reported that high miR-125b expression in tissue and serum was associated with a poor treatment response in locally advanced rectal cancer (30). Interestingly, Tanaka et al identified miR-125b-1 expression in cancer tissues as a predictive biomarker for the efficacy of peptide vaccine treatment against CRC (31). However, our study is the first to demonstrate the potential of plasma ex-miR-125b as a biomarker for the early detection of resistance to mFOLFOX6-based chemotherapy in advanced/recurrent CRC.…”
Section: Discussionmentioning
confidence: 61%
“…118 The field is therefore moving along three non-mutually exclusive directions: (1) combining peptide-based vaccination with additional forms of (immuno)therapy, with the specific aim of reverting immunosuppression and enabling therapeutically relevant immune responses, 270-272 (2) targeting private antigenic epitopes that originate from mutations affecting only malignant cells (or sub-populations thereof), with PPV, 167,272-275 and (3) identifying specific patient populations that may obtain clinical benefit from the use of peptide-based vaccination. 174,254 Although the feasibility of PPV on a large scale remains unclear, we surmise combining some variants of peptide-based vaccination with potent immunostimulatory agents including immune checkpoint blockers and oncolytic viruses may be the key to unlock the true potential of this hitherto unrealized therapeutic modality.…”
Section: Discussionmentioning
confidence: 99%
“…The specific function of them determines whether or not cells undergo apoptosis. To a certain extent, apoptosis or apoptosis inhibition is determined by gene regulation (20).…”
Section: Discussionmentioning
confidence: 99%